KAJIAN PUSTAKA POTENSI PEMANFAATAN GREYWATERSEBAGAI AIR SIRAM WC DAN AIR SIRAM TANAMAN DI RUMAH TANGGA - Handayani, Dwi Siwi (Universitas Diponegoro, 2013)
ABSTRACT The level of water service coverage in Indonesia is less than 60 % at 2011. The one reason is because of the scarcity of raw water both in quantity and quality. Besides the level of service coverage, Indonesia face to the environmental degradation specially Pantura area with landsubsidence and abrassion by the sea water. It is because of over extraction of groundwater to fulfill water demand people who did not served by PDAM. Indonesia also not yet give attention on wastewater services. Mostly of greywater goes enterto waterbody directly without treatment through drainage system. So, to economize on using clean water and to crack the greywater goes enter to drainage system is very important to do immediately by using greywater as substitute of water toilet flushing and gardening irrigation. Greywater is domestic waste water excluded feces and urine. Many country have already been using greywater for toilets flushing and gardening irrigation. The aim of this studi is to know potentially of greywater as toilets flushing and gardening irrigation. The method for data collecting is documentation method with descriptif analysis data method. The results is thatthe quantity greywater generated from bathing each person per day can fulfill demand of toilets flushing each person per day. The greywater generated from home laundry can fulfill demand of gardening irrigation. But there are some challangespotentially to conduct reusing greywater as toilets flushing and gardening irrigation, such as negativeperception on using it, difficulties on storage it, etc. So, many research topics to cope these challanges have been identified in this study..Keywords: greywater, toilets flushing, gardening irrigation